Exercise induced arterial hypoxemia in swimmers - Spandoudaki, S. S.; maridaki, M. D.; Myrianthefs, P. M.; Baltopoulos, P. J. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Exercise induced arterial hypoxemia (EIAH) is a reduction in arterial oxygenation, which may result from a drop in arterial oxygen pressure and therefore in oxygen saturation. We examined EIAH in swimmers, while till now it was known to occur in cyclists and runners. METHODS: We studied 8 male highly trained swimmers (age: 23+/-1.7; (.-)VO(2peak), 5.3+/-0.1 l/min and 8 male ex-swimmers (age: 21.5+/-0.6; (.-)VO(2peak), 3.4+/-0.3 l/min). All subjects performed 200-meter freestyle at maximum effort. Hemoglobin saturation (SaO(2)%) was measured using a finger pulse oximeter before exercise in the water in an upright position and immediately after exercise, within 5 seconds. RESULTS: Highly trained swimmers developed a statistically significant decrease in SaO(2)% (from 98.3+/-0.3 to 94+/-0.9, p= or <0.01) after exercise, while ex-swimmers did not (from 98.4+/-0.3 to 96.8+/-0.3 ns). The 4% decrease in SaO(2)% observed in highly trained swimmers can be characterized as mild EIAH. CONCLUSIONS: Our study suggests that highly trained swimmers but not ex-swimmers may develop mild EIAH after 200 meters freestyle swimming at maximum effort.